Timing sentiment with style: Evidence from mutual funds - Zheng, Yao; Osmer, Eric; Zu, Dingding (Journal of Banking & Finance, 2024)
This study analyzes four distinct types of mutual fund sentiment timing skills using a multifactor framework. Our results indicate a diminished significance of market sentiment timing, in contrast to the results of prior studies. Additionally, we reveal that size and value sentiment timing can substantially enhance fund performance. Managers strategically reduce their exposure to small stocks using size sentiment timing and increase exposure to value stocks through value sentiment timing during high sentiment periods. We find no evidence that mutual fund managers engage in momentum sentiment timing.